LEGALISTIC PERSPECTIVE: ANALYSIS OF COMMUNITY POLITICAL PARTICIPATION IN THE 2018 ELECTION IN THE MAIWA DISTRICT, ENREKANG DISTRICT (Institut Pemerintahan Dalam Negeri, 2020)
This research discusses the legalistic review of Community political participation in the 2018 concurrent elections in the Maiwa district of Enrekang subdistrict which was set forth in the regulation of the General Election Commission number 8 year 2017. This research is a qualitative descriptive study where researchers conduct interviews and collect documents relating to research topics. The interviews were conducted to the Committee for electoral organizers (PPK) and society. The results showed that judging by the legalistic reviews of public political participation in the 2018 concurrent elections in the Maiwa district of Enrekang subdistrict was not good enough. This refers to the 4 (four) aspects of community involvement in the elections, supervision at each stage of election, socialization of elections and political education for voters., which is set forth in the regulation of the General Elections Commission Number 8 year 2017. In the aspect of community involvement in the election and supervision of elections has been implemented by the Community and supervisory organizations in the district Maiwa but for aspects of socialization and political education for the society has not been effective enough Conducted by the Committee of electoral organizers. The advice can be given by researchers, among others: Should the organizers of the elections can improve the performance in the electoral process, especially in logging voters by way of re-checking the community data before Election was implemented. Furthermore, PPK is expected to increase the quantity and quality of socialization and political education, by arranging a clear schedule so that the socialization material can be precise. PPK can also approach the community by creating ϐlyers or information related to elections that can be disseminated to the public in both printed and electronic forms. Keywords: legalistic, political participation, elections